Museutopia : Schritte in andere Welten - Badura, Michael; Brendel, Micha; Caniaris, Vlassis; Craig, Stephen; Creischer, Alice; Dion, Mark; Eckert, Günther, L.; Fisahn, Maria; Grashorn, Burkhard; Gudjonsdottir, Anna; Haarmann, Anke; Hayes, Cameron; et al. (Hagen : Karl Ernst Osthaus-Museum, 2003)
Badura, Michael ; Brendel, Micha ; Caniaris, Vlassis ; Craig, Stephen ; Creischer, Alice ; Dion, Mark ; finger ; Fisahn, Maria ; Galerie für Landschaftskunst ; Grashorn, Burkhard ; Haarmann, Anke ; Hayes, Cameron ; Helguera, Pablo ; IRWIN ; Kamphusmann, Thomas ; Karrenberg, Katharina ; Knaust, Rainer ; Marjanov, Wasa ; The Martynchiks ; Martynchik, Svetlana ; Stepin, Igor ; Meyer-Rogge, Jan ; Museum of Jurassic Technology ; Van Geluwe, Johan ; Przyjemski, Leszek ; Nicolai, Olaf ; Pircher, Wolfgang ; Pitzen, Marianne ; Reichert, Johannes ; Salon de Fleurus ; Schulz, Tilo ; Seid, Dui ; Siebeck, Oliver ; Sigurdsson, Sigrid ; Siekmann, Andreas ; Silber, Alex ; Siler, Todd ; Ulrichs, Timm ; de Vries, Herman ; Walgenbach, Judith ; Wexler, Allan ; Wurmfeld, Hope Herman ; Zinsmeister, Annett
biog. p. 229-244
Duits
Museutopia - Schritte in andere Welten, Karl Ernst Osthaus-Museum, Hagen, 09.06.2002 - 31.10.2002.
boek